Pengaruh Penerapan Sistem Administrasi Perpajakan Modern, Kualitas Pelayanan Dan Kesadaran Wajib Pajak Pada Kepatuhan WPOP - Yunika Antari, Ni Luh Putu; Supadmi, Ni Luh (E-Jurnal Akuntansi; Vol 26 No 1 (2019), 2019)
The purpose of this study was to determine the effect of the application of a modern tax administration system, service quality, and taxpayer awareness on individual taxpayer compliance (WPOP). This research was conducted at KPP Pratama Denpasar Timur. The data analysis technique used is multiple linear regression. Based on the results of the analysis obtained a modern tax administration system, service quality, and awareness of taxpayers have a positive and significant effect on WPOP compliance. This shows that if the tax administration system is implemented well, it will tend to increase compliance with WPOP reporting. Service quality also has a positive effect on WPOP compliance, this proves that the better the quality of services provided will make the taxpayer more compliant in fulfilling his obligations. Keywords : modern tax administration system, service quality, and taxpayer awareness